1989
DOI: 10.1021/bi00444a044
|View full text |Cite
|
Sign up to set email alerts
|

Spin-label ESR studies of lipid-protein interactions in thylakoid membranes

Abstract: Lipid-protein interactions in thylakoid membranes, and in the subthylakoid membrane fractions containing either photosystem 1 or photosystem 2, have been studied by using spin-labeled analogues of the thylakoid membrane lipid components, monogalactosyldiacylglycerol, phosphatidylglycerol, and phosphatidylcholine. The electron spin resonance spectra of the spin-labeled lipids all consist of two components, one corresponding to the fluid lipid environment in the membranes and the other to the motionally restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
39
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…9 and 38. The association constant of SASL relative to MGDG in thylakoid membranes can be estimated from that of SASL and MGDG observed relative to phosphatidylglycerol (21,39) to be K r ϭ Ϸ6.5. With these estimates the values of n are 1.0, 1.1, 0.6, 1, and 2.7 for 0.5, 6, 12, 24, and 48 h of greening, respectively.…”
Section: Spin Label Epr Spectroscopy Of Acyl Chain Mobility and Lipidmentioning
confidence: 99%
See 3 more Smart Citations
“…9 and 38. The association constant of SASL relative to MGDG in thylakoid membranes can be estimated from that of SASL and MGDG observed relative to phosphatidylglycerol (21,39) to be K r ϭ Ϸ6.5. With these estimates the values of n are 1.0, 1.1, 0.6, 1, and 2.7 for 0.5, 6, 12, 24, and 48 h of greening, respectively.…”
Section: Spin Label Epr Spectroscopy Of Acyl Chain Mobility and Lipidmentioning
confidence: 99%
“…The immobile component was assigned to protein-solvating interfacial lipids (38,39). Because the outer hyperfine splitting of the components differed by more than 5 G, we could determine the immobile fraction ( f i,SASL ) by applying an intersubtraction technique (21,40) on the 34°C spectra, aided with nonlinear least-squares optimization. The intersubtraction leads to excellent fits between the linear combination of the two components and the experimental spectra (Fig.…”
Section: Spin Label Epr Spectroscopy Of Acyl Chain Mobility and Lipidmentioning
confidence: 99%
See 2 more Smart Citations
“…Electron spin resonance studies of Li et al (20) have reported that a unique feature of thylakoid membranes is the specificity of interaction of thylakoid PG for thylakoid proteins. PG has been found to be localized primarily in the outer layer of the thylakoid bilayer (22).…”
mentioning
confidence: 99%